2019
DOI: 10.35940/ijrte.b1187.0782s319
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research of Wall Pressure Distribution and Effect of Micro Jet at Mach 1.5

Abstract: In this paper, a study on the effect of the control on the wall pressure as well as the quality of the flow when tiny jets were employed. The small jet aimed to regulate the base pressure at the base region of the suddenly expanded duct and wall pressure distribution is carried out experimentally. The convergent-divergent (CD) nozzle with a suddenly expanded duct was designed to observe the wall pressure distribution with and without control using small jets. In order to obtain the results with the effect of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The boat tail helmets can reduce drag studied by Pathan et al, [21] and found that the aerodynamic drag reduces when the helmet shape is streamlined. Azami et al, [22] explored the experimental research of wall pressure and the effect of microjet. The base pressure variation in external and internal flows using CFD analysis is studied by Pathan et al, [23] and revealed that the internal and external suddenly expanded flows are nearly the same in the base region of the flow field.…”
Section: Fig 1 Geometry Of Conementioning
confidence: 99%
“…The boat tail helmets can reduce drag studied by Pathan et al, [21] and found that the aerodynamic drag reduces when the helmet shape is streamlined. Azami et al, [22] explored the experimental research of wall pressure and the effect of microjet. The base pressure variation in external and internal flows using CFD analysis is studied by Pathan et al, [23] and revealed that the internal and external suddenly expanded flows are nearly the same in the base region of the flow field.…”
Section: Fig 1 Geometry Of Conementioning
confidence: 99%
“…Azami et al, [16,17] studied the control of suddenly expanded flows with micro-jets, an active control using an experimental method. The experiment proves that micro-jet manages to significantly base pressure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Whenever the control mechanism is employed, either passive or active, it is mandatory on the part of the researcher to monitor the static pressure at the duct surface and flow field in a suddenly expanded duct. The wall pressure distribution has been reported for different Mach numbers [10][11][12][13][14]. The primary observation of wall pressure is based on the Mach number variation and area ratio in their reviews.…”
Section: Literature Reviewmentioning
confidence: 99%